Susceptibility of Escherichia coli to C2-C18 fatty acids - Marounek, M; Skrivanová, E; Rada, V (Folia microbiologica, 2003)
The antimicrobial activity of C2-C18 fatty acids was determined in vitro in cultures of two strains of Escherichia coli grown on glucose. Antimicrobial activity was expressed as IC50 (a concentration at which only 50% of the initial glucose in the cultures was utilized). Utilization of glucose was inhibited by caprylic acid (IC50 0.30-0.85 g/L) and capric acid (IC50 1.25-2.03 g/L). Neither short-chain fatty acids (C2-C6) nor fatty acids with longer chain (C12-C18) influenced substrate utilization. Caproic acid, however, decreased cell yield in cultures of E. coli in a dose-dependent manner. No inhibition of glucose utilization was produced with unsaturated fatty acids, oleic and linoleic. Calcium ions added in excess reversed the antimicrobial effect of capric acid, but not that of caprylic acid. Antimicrobial activity of caprylic and capric acid decreased when the bacteria were grown in the presence of straw particles, or repeatedly subcultured in a medium containing these compounds at low concentrations. Counts of viable bacteria determined by plating decreased after incubation with caprylic and capric acid (30 min; 1 g/L) at pH 5.2 from > 10(9) to approximately 10(2)/mL. A reduction of a mere 0.94-1.96 log10 CFU was observed at pH 6.5-6.6. It can be concluded that caprylic acid, and to a lesser extent also capric acid, has a significant antimicrobial activity toward E. coli. Effects of other fatty acids were not significant or absent.
Keywords: kyseliny dekanové; Antifungal Agents; Calcium; Caprylates; Culture Media; kapryláty; kultivační média; vápník; mastné kyseliny; Drug Resistance, Bacterial; techniky in vitro; antifungální látky; Hydrogen-Ion Concentration; Escherichia coli; Fatty Acids; koncentrace vodíkových iontů; Decanoic Acids; bakteriální léková rezistence; In Vitro Techniques